The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1037/emo0001187
|View full text |Cite
|
Sign up to set email alerts
|

Awe fosters global self-continuity: The mediating effect of global processing and narrative.

Abstract: Awe is a self-relevant emotion, but whether and how awe impacts global self-continuity (GSC), a sense of connectedness among past, present, and future selves, has never been investigated. In six studies (N = 1,384), we examined the relationship between awe and GSC, as well as the mechanisms underlying this relationship, with both correlational and experimental design. We found awe positively associated with (Studies 1 and 3) and predicted (Studies 2 and 4–6) GSC. Moreover, we found that global processing (proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Mediation analysis does not require both significant a and b coefficients (e.g., MacKinnon et al, 2002; Preacher & Hayes, 2004). Therefore, although without preregistration, we dissociated the effects of awe per se on dependent variables from threat-based awe by conducting a series of parallel mediation, which included awe and fear index as the parallel mediators (Pan & Jiang, 2022). We also reported the results following the preregistered analysis plans.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mediation analysis does not require both significant a and b coefficients (e.g., MacKinnon et al, 2002; Preacher & Hayes, 2004). Therefore, although without preregistration, we dissociated the effects of awe per se on dependent variables from threat-based awe by conducting a series of parallel mediation, which included awe and fear index as the parallel mediators (Pan & Jiang, 2022). We also reported the results following the preregistered analysis plans.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to examine the effects of the emotion of awe per se, researchers have attempted to separate awe's effects from the co-occurring emotions statistically or experimentally (e.g., Bai et al, 2017Bai et al, , 2021T. Jiang & Sedikides, 2022;Pan & Jiang, 2022;Piff et al, 2015).…”
Section: Awe and Meaning In Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the differences in level, abundant literature suggested that both state and trait awe exhibit the same effects on many kinds of outcomes, including self-smallness, authentic-self pursuit, life satisfaction, global selfcontinuity, and prosocial behavior (e.g., Bai et al, 2017Bai et al, , 2021T. Jiang & Sedikides, 2022;Pan & Jiang, 2022;Piff et al, 2015). Therefore, in the current research, we aimed to test the possible effect of awe on self-humanity both at the state (Studies 2a, 2b, 3, 5, and 6) and trait (Studies 1 and 4) levels.…”
Section: Overview Of the Present Researchmentioning
confidence: 99%
“…However, some have also challenged and criticized this perspective (for details, see Perlin & Li, 2020). Recently, another line of research complemented this perspective by arguing that awe can inspire authentic-self pursuit via self-transcendence (e.g., T. Jiang & Sedikides, 2022) and that self-smallness is not the only way for awe to shape self-perception (e.g., Pan & Jiang, 2022). Our results align with the perspective of self-transcendence, where awe increases the humanness one perceives in oneself; this effect can be explained by authentic-self pursuit rather than self-smallness.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%